Expression profile in rice panicle: insights into heat response mechanism at reproductive stage. - Xianwen Zhang (Public Library of Science (PLoS), 2012)
Rice at reproductive stage is more sensitive to environmental changes, and little is known about the mechanism of heat response in rice panicle. Here, using rice microarray, we provided a time course gene expression profile of rice panicle at anther developmental stage 8 after 40°C treatment for 0 min, 20 min, 60 min, 2 h, 4 h, and 8 h. The identified differentially expressed genes were mainly involved in transcriptional regulation, transport, cellular homeostasis, and stress response. The predominant transcription factor gene families responsive to heat stress were Hsf, NAC, AP2/ERF, WRKY, MYB, and C(2)H(2). KMC analysis discovered the time-dependent gene expression pattern under heat stress. The motif co-occurrence analysis on the promoters of genes from an early up-regulated cluster showed the important roles of GCC box, HSE, ABRE, and CE3 in response to heat stress. The regulation model central to ROS combined with transcriptome and ROS quantification data in rice panicle indicated the great importance to maintain ROS balance and the existence of wide cross-talk in heat response. The present study increased our understanding of the heat response in rice panicle and provided good candidate genes for crop improvement.